Unsteady Architecture: Ambiguity, the Senate Reference, and the Future of Constitutional Amendment in Canada - Macfarlane, Emmett (McGill Law Journal / Revue de droit de McGill, 2015)
This article critically examines the Supreme Court of Canada’s opinion in the Senate Reform Reference from the perspective of its coherence in interpreting the various amending procedures in Part V of the Constitution Act, 1982. It analyzes the ways that the underlying logic of the Court’s reasoning, particularly with respect to the method of selecting senators and senatorial term limits, creates ambiguity and risks unintended consequences for future attempts at constitutional amendment. The Court’s explicit refusal to distinguish between the federal government’s unilateral ability to enact a retirement age and its logic that term limits, regardless of length, require the consent of the provinces under the general amending procedure lacks logical consistency and arguably erodes the unilateral amending procedure to a problematic degree. In the context of its reasoning with respect to changes to the method of selecting senators, the Court’s reliance on the amorphous notion of the “constitutional architecture” clouds the definable limits of “method of selection” under section 42(1)(b). The Senate Reform Reference introduces considerable ambiguity into what changes the federal executive can implement with respect to the appointments process itself. The article concludes by exploring the political implications that the decision has for the future of Senate reform specifically and for our ability to amend the constitution generally.